Asymmetric Transmission From Producer Price To Food Consumer Price - Oral, Orkun; Eştürk, Özlem (Fırat University, 2022)
Global food prices are affected from the increase in input costs as well as the disruptions in the supply chain during the Covid-19 epidemic and the problems experienced in agricultural production due to climate change. Concerns about global food supply and food price increases were among the priority agendas of governments. The aim of this study was to examine the relationship between general producer inflation and food consumer inflation for the period of 2006-2021 in Turkey, within the framework of short and long-term asymmetric dynamics. In this context, the short and long term asymmetric effects of producer price index (PPI) on food and non-alcoholic beverages index, which included in consumer price index (CPI), were analyzed with the help of NARDL model by using monthly data for the period 2006-2021. According to the results of the study, it was concluded that the shocks of the PPI in the Turkish economy had an asymmetric effect on the CPI and the positive shocks in the PPI index had a higher impact than the negative shocks in the 2006-2021 period. An 1% negative shock in the PPI caused an increase of 0.92% in the CPI, and the 1% positive shock caused an increase of 0.33% in the CPI. In this context, it was concluded that arrangements and measures should be planned in long term in order to eliminate the impact of the increases in PPI on the CPI.

İklim değişikliğinin, son yıllarda tarımsal üretimde yol açtığı problemlerin yanı sıra, Covid-19 salgın sürecinin tedarik zincirinde aksamalara neden olması ve girdi maliyetlerindeki artışlar küresel gıda fiyatlarını yükseltmiştir. Küresel gıda arzında yaşanan kaygılar ve gıda fiyat artışları hükümetlerin öncelikli gündemleri arasında yer almıştır. Bu çalışmada, Türkiye’nin 2006-2021 dönemi için genel üretici enflasyonu ile gıda tüketici enflasyonu arasındaki ilişkinin, kısa ve uzun dönem asimetrik dinamikler çerçevesinde incelenmesi amaçlanmıştır. Bu kapsamda, 2006-2021 dönemine ait aylık veriler kullanılarak, üretici fiyatı endeksinin (ÜFE), tüketici fiyat endeksi (TÜFE) içerisinde yer alan gıda ve alkolsüz içecekler endeksi üzerindeki kısa ve uzun dönem asimetrik etkileri NARDL modeli yardımıyla analiz edilmiştir. Çalışmadan edilen bulgulara göre, Türkiye ekonomisinde 2006-2021 döneminde ÜFE’de meydana gelen şokların TÜFE üzerinde asimetrik etkiye sahip olduğu, ÜFE endeksinde gerçekleşen pozitif şokların negatif şoklara kıyasla daha yüksek etki sergilediği sonucuna ulaşılmıştır. ÜFE’de meydana gelen %1’lik negatif şok TÜFE üzerinde %0,92’lik bir artışa, %1’lik pozitif şok ise TÜFE %0,33’lük artışa neden olmuştur. Bu kapsamda, ÜFE’de meydana gelen yükselişlerin TÜFE üzerindeki etkisinin giderilmesi adına yapılacak düzenlemelerin ve alınacak önlemlerin uzun dönemli planlanması gerektiği vurgulanabilir.
ÜRETİCİ FİYATINDAN GIDA TÜKETİCİ FİYATINA ASİMETRİK İLETİM